Respostas
respondido por:
0
x^2-5x+6=0
delta=b^2-4ac
delta=(-5)^2-4.1.6
delta=25-24
delta=1
x=-b-/+ raiz de delta/2a
x=-(-5)-1/2.1
x=5-1/2
x=4/2
x=2
x=-(-5)+1/2.1
x=5+1/2
x=6/2
x=3
S={2, 3}
delta=b^2-4ac
delta=(-5)^2-4.1.6
delta=25-24
delta=1
x=-b-/+ raiz de delta/2a
x=-(-5)-1/2.1
x=5-1/2
x=4/2
x=2
x=-(-5)+1/2.1
x=5+1/2
x=6/2
x=3
S={2, 3}
respondido por:
0
Resposta:
ja fiz essa
Explicação passo-a-passo:
x^2-5x+6=0
delta=b^2-4ac
delta=(-5)^2-4.1.6
delta=25-24
delta=1
x=-b-/+ raiz de delta/2a
x=-(-5)-1/2.1
x=5-1/2
x=4/2
x=2
x=-(-5)+1/2.1
x=5+1/2
x=6/2
x=3
S={2, 3}
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás